FORMULASI BUBUR INSTAN KOMBINASI TEMPE DAN RUMPUT LAUT SERTA EFEK SINERGISMENYA TERHADAP KOLESTEROL DARAH - Syamsuri Syakri; Natsir Djide; Faisal Attamimi (Fakultas Farmasi UMI, 2014)
Formulation of Instant Porridge as the combination of Tempe and seaweed and its Synergism Effect Of Cholesterol level Blood. The aim of the research is to make instant porridge as the combination of tempe and seaweed which could be used as a food alternative and its influence on patients cholesterol and the determine a suitable formulation in making instant porridge as the combination of tempe and seaweed. The absorption was measured by using photometer 5010 with a long unbroken wave 546 nm. The statictical analysis reveal that instant porridge as the combination of tempe and seaweed could decrease cholesterol in which decrease of cholesterol really differs among formulation 1,2, and 3. The one in formulation 2 is 50%, and the one formulation 3 is 40%. The effect of synergism occurs in formulation 2, i.e 50% in which the comparison of tempe and seaweed is 50 : 50. Hedonic test by 10 respondents proves that all the respondents like instant porridge as the combination of tempe and seaweed about colour, aroma, taste, and texture. Key word : Instant Porridge, Formulation, Cholesterol, Seaweed, Tempe